Detection of risk of cancer to man. - Peto, R (1979)
Epidemiology can pick out large-scale determinants of human cancer, such as smoking. Also, epidemiology can pick out carcinogens such as asbestos to which groups of perhaps a few hundred or a few thousand workers have been heavily exposed for decades. However, if highly exposed groups cannot be studied then epidemiology cannot recognize carcinogens which, although perhaps widely distributed, produce only a small percentage increase in particular cancers. Almost all of the environmental pollutants that can affect human cancer incidence will do so only to a very minor extent, at the levels to which we are currently exposed. For this reason, and also because it is often difficult to define an exposed and an unexposed group which do not differ in other ways as well, it will almost always be impossible to do anything epidemiologically except to set a very crude upper limit on their likely hazards. The only way, therefore, to get any direct estimate of these hazards is by laboratory studies of the effects of high doses on various model systems. For this and for other reasons, it would be highly desirable to have good laboratory models for human carcinogenesis. The characteristics required of satisfactory laboratory systems are reviewed, and it is argued that systematic errors may arise unless one studies epithelial cells from large, long-lived species under conditions of chronic, low-dose exposure to noxious test agents in conjunction with standard chronic doses of agents which may be synergistic with the test agents. (Carcinogenic mutagens may be synergistic with carcinogenic non-mutagens.) For reasons of expense and speed, such studies must be done in vitro. If such in-vitro systems can be developed, either by using tissue explants or cell cultures, an important criterion which they will have to satisfy to be trusted will be that under chronic exposure the rate of transformation should be proportional to something like the fourth power of exposure duration. This paper chiefly reviews the reasons for choosing these specifications for a trustworthy in-vitro model for human carcinogenesis.